Citizenship and the Social Integration of Immigrants: Evidence from Germany's Immigration Reforms - Nicolas Keller; Christina Gathmann; Ole Monscheuer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study whether the option to naturalize improves social and cultural integration of immigrants in the host country. The empirical analysis relies on two immigration reforms in Germany, a country with a traditionally weak record of immigrant integration both in terms of labor market performance but also social integration. For identi
Keywords: J13; J01; J18; 330